Comparison of Coronally Advanced Flap with Semilunar Coronally Repositioned Flap with Sutures for the Treatment of Gingival Recession (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: The surgical correction of shallow gingival recession by coronally advanced flap (CAF) and its variant semilunar coronally repositioned flap (SLF) offers the advantage of a single surgical site, less patient discomfort and predictable root coverage with good colour match. This study aims to compare and evaluate the predictability and reliability of the two types of flaps.Methods: In 20 Miller’s Class I recession defects, 10 sites each were treated with either SLF or CAF. Recession height, recession width, clinical attachment loss, width of keratinized gingiva, Plaque Index and Gingival Index were assessed at baseline, 1, 3 and 6 months. The intra-group comparison was done using paired t-test and the inter-group comparison using independent t-test with statistical p value set at